Pengaruh Penggunaan Bahan Ajar Berbasis Android dan Tipe Kepribadian Terhadap Kemampuan Komunikasi Matematis Calon Guru - Makur, Alberta Parinters; Kurniawan, Yohanes; Gunur, Bedilius (UIN Sunan Ampel Surabaya, 2018)
This research aims to determine the effect of using an android application compared to conventional teaching materials on Trigonometry courses on the mathematical communication skills of student candidates regarding personality type. The research method was used quasi-experiment with the population of first grade at Department of Mathematics Education of STKIP Santu Paulus Ruteng and the sample was taken from 2 classes. Data were through by questionnaires and mathematical communication test which were then analyzed by two-way ANOVA test. Data analysis and interpretation showed that: (1) students who were taught using the help of Android-based teaching materials had better mathematical communication skills than students taught conventionally; (2) there was an interaction between learning media and personality type on mathematical communication skills. The findings point to recommendations that the use of appropriate instructional media could be used to improve students' mathematical communication skills and would facilitate the learning process of mathematics.